Sosialisasi Penanganan Pertama Luka Bakar di Rumah bagi Masyarakat Banjarmasin: Socialization of First Aid Home Treatment for Burns in Banjarmasin Community - Trifianingsih, Dyah; Sitompul, Dania Relina; Rachman, Aulia (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Proper treatment of burns can reduce pain, prevent infection, and accelerate wound healing. Burns that do not receive proper and immediate treatment due to a lack of public knowledge can cause various complications such as infection, shock, and electrolyte imbalance and can be followed by severe psychological trauma due to disability caused by burn scars. This community service aims to increase community knowledge and skills in first aid for burns. The methods used in this community service program include providing health education with lectures and demonstrations of the initial treatment of burn wounds. The Community service was carried out on June 19, 2023. The target of the activity was the community in the Sungai Baru Village Area, Banjarmasin. Community service activities begin with a lecture regarding the concept and treatment of burn wounds, followed by demonstrating techniques for treating burn wounds, and closed with a question and answer session. This activity was evaluated by giving questionnaires before and after providing health education to participants. The results of this activity showed an increase in participants' knowledge of treating burns. This activity increased participants' knowledge of treating burns. Based on these results, there is hope that people will be careful to avoid burns and can provide appropriate burn aid according to the severity.